Phase-field modeling of microstructural pattern formation in alloys and geological veins - Ankit, Kumar (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2016)
With the advent of high performance computing, the application areas of the phase-field method, traditionally used to numerically model the phase transformation in metals and alloys, have now spanned into geoscience. A systematic investigation of the two distinct scientific problems in consideration suggest a strong influence of interfacial energy on the natural and induced pattern formation in diffusion-controlled regime.